2001
DOI: 10.1200/jco.2001.19.10.2647
|View full text |Cite
|
Sign up to set email alerts
|

Viable Malignant Cells After Primary Chemotherapy for Disseminated Nonseminomatous Germ Cell Tumors: Prognostic Factors and Role of Postsurgery Chemotherapy—Results From an International Study Group

Abstract: A complete resection may be more critical than recourse to postoperative chemotherapy in the setting of postchemotherapy viable malignant NSGCT. Immediate postoperative chemotherapy or surveillance alone with chemotherapy at relapse may be reasonable options depending on the completeness of resection, IGCCC group, and percent of viable cells. Validation is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
3
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(130 citation statements)
references
References 40 publications
6
111
3
9
Order By: Relevance
“…[3][4][5][6][7][8] Metastatic mature teratoma is usually treated by surgery alone, whereas the presence of yolk sac tumor requires additional neoadjuvant therapy. [33][34][35] Proliferative or hyperplastic endodermal glandular epithelium of teratoma or rare somatic adenocarcinoma arising from teratoma can mimic glandular yolk sac tumor. [3][4][5][6][7][8] Myxoid/reticular/microcystic yolk sac tumor may also be mistaken as edematous mesodermal teratomatous element or embryonal carcinoma-associated stroma, in particular when yolk sac tumor and embryonal carcinoma/teratoma are intimately associated.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Metastatic mature teratoma is usually treated by surgery alone, whereas the presence of yolk sac tumor requires additional neoadjuvant therapy. [33][34][35] Proliferative or hyperplastic endodermal glandular epithelium of teratoma or rare somatic adenocarcinoma arising from teratoma can mimic glandular yolk sac tumor. [3][4][5][6][7][8] Myxoid/reticular/microcystic yolk sac tumor may also be mistaken as edematous mesodermal teratomatous element or embryonal carcinoma-associated stroma, in particular when yolk sac tumor and embryonal carcinoma/teratoma are intimately associated.…”
Section: Discussionmentioning
confidence: 99%
“…Fizazi et al hebben de distributie van metastasering onderzocht bij 238 patiënten nadat deze waren behandeld met chemotherapie. Zij hadden metastasen in retroperitoneale lymfeklieren (83 %), longen (27 %), mediastinum (15 %), cervicale lymfeklieren (4 %), lever (2 %), bot (1 %) en hersenen (0,5 %) [2]. Indien er sprake is van metastasering kan een multimodaliteitsbehandeling met multipele BEP-kuren in combina-…”
Section: Samenvattingunclassified
“…Steyerber, et al reported that histology at residual retroperitoneal lymph node dissection (RPLND) was a strong predictor of histology at thoracotomy (38). However, several authors have reported pathology from residual RPLND to differ from pathology from residual pulmonary nodules in as high as 30% of cases (39)(40)(41)(42). Therefore, pulmonary metastatectomy should be at least considered even in cases with necrosis or fibrosis on RPLND.…”
Section: Germ Cell Tumoursmentioning
confidence: 99%